Central venous-to-arterial carbon dioxide difference and the effect of venous hyperoxia: A limiting factor, or an additional marker of severity in shock? - Saludes, P.; Proença, L.; Gruartmoner, G.; Enseñat, L.; Pérez-Madrigal, A.; Espinal, C.; Mesquida, J. (Journal of clinical monitoring and computing, 2017)
Central venous-to-arterial carbon dioxide difference (P cva CO 2 ) has demonstrated its prognostic value in critically ill patients suffering from shock, and current expert recommendations advocate for further resuscitation interventions when P cva CO 2 is elevated. P cva CO 2 combination with arterial–venous oxygen content difference (P cva CO 2 /C av O 2 ) seems to enhance its performance when assessing anaerobic metabolism. However, the fact that PCO 2 values might be altered by changes in blood O 2 content (the Haldane effect), has been presented as a limitation of PCO 2 -derived variables. The present study aimed at exploring the impact of hyperoxia on P cva CO 2 and P cva CO 2 /C av O 2 during the early phase of shock. Prospective interventional study. Ventilated patients suffering from shock within the first 24 h of ICU admission. Patients requiring FiO 2 ≥ 0.5 were excluded. At inclusion, simultaneous arterial and central venous blood samples were collected. Patients underwent a hyperoxygenation test (5 min of FiO 2 100%), and arterial and central venous blood samples were repeated. Oxygenation and CO 2 variables were calculated at both time points. Twenty patients were studied. The main cause of shock was septic shock (70%). The hyperoxygenation trial increased oxygenation parameters in arterial and venous blood, whereas PCO 2 only changed at the venous site. Resulting P cva CO 2 and P cva CO 2 /C av O 2 significantly increased [6.8 (4.9, 8.1) vs. 7.6 (6.7, 8.5) mmHg, p 0.001; and 1.9 (1.4, 2.2) vs. 2.3 (1.8, 3), p < 0.001, respectively]. Baseline P cva CO 2 , P cva CO 2 /C av O 2 and S cv O 2 correlated with the magnitude of PO 2 augmentation at the venous site within the trial ( ρ −0.46, p 0.04; ρ 0.6, p < 0.01; and ρ 0.7, p < 0.001, respectively). Increased P cva CO 2 /C av O 2 values were associated with higher mortality in our sample [1.46 (1.21, 1.89) survivors vs. 2.23 (1.86, 2.8) non-survivors, p < 0.01]. P cva CO 2 and P cva CO 2 /C av O 2 are influenced by oxygenation changes not related to flow. Elevated P cva CO 2 and P cva CO 2 /C av O 2 values might not only derive from cardiac output inadequacy, but also from venous hyperoxia. Elevated P cva CO 2 /C av O 2 values were associated with higher PO 2 transmission to the venous compartment, suggesting higher shunting phenomena.